MOF Regulates TNK2 Transcription Expression to Promote Cell Proliferation in Thyroid Cancer - Li, Danyang; Yang, Yang; Chen, Bo; Guo, Xinghong; Gao, Shuang; Wang, Meng; Duan, Mingxiao; Li, Xiangzhi (Frontiers in Pharmacology, 2020)
MOF is a well-known histone acetyltransferase to catalyze acetylation of histone H4 lysine 16 (K16), and it is relevant to diverse biological processes, such as gene transcription, cell cycle, early embryonic development and tumorigenesis. Here, we identify MOF as an oncogene in most thyroid cancer. It is found that expression level of MOF was significantly upregulated in most thyroid cancer tissue samples and cell lines. MOF-deficient in both BHP-10-3 and TT2609 cell lines inhibited cell proliferation by blocking the cell cycle in G1 phase and enhanced cell apoptosis. Mechanistically, MOF bound the TNK2 promoter to activate TNK2 transcription. Furthermore, the expression level of TNK2 was decreased with the histone acetyltransferase inhibitor. Besides, MOF promoted proliferation of thyroid cancer cells through increased phosphorylation of AKT, thus activating the PI3K/AKT pathway. Ultimately, our findings indicated that MOF played an oncogene role in development and progression of thyroid cancer and may be a potential novel target for the treatment of thyroid cancer.